Pengaruh Idealisme, Kecerdasan Emosional dan Etika pada Persepsi Etis Mahasiswa Profesi Akuntansi dengan Kepercayaan Diri - Listya Adriani Sidartha, Ayu; Sujana, I Ketut (E-Jurnal Akuntansi, 2020)
This study aims to determine the influence of idealism, emotional intelligence and ethics on the ethical perceptions of accounting profession students regarding the ethical behavior of accountants with self-confidence as a moderating factor. The population in this study Accounting Professional Education Students (PPAk) and the total sample of 40 accounting profession students using the technique of determining the sample of saturated data. The data analysis technique used is Moderated Regression Analysis. The results of this study indicate that idealism, emotional intelligence and ethics have a significant positive effect on the ethical perceptions of accounting profession students regarding the ethical behavior of accountants and the results of research on self-confidence as a moderating variable, showing that self-confidence is able to strengthen the influence of idealism, emotional intelligence and ethics on ethical perception accounting profession students regarding the ethical behavior of accountants. Keywords: Idealism; Emotional Intelligence; Ethics; Ethical Perception; Confidence.